CATEGORY OF HEDGING USED ON SUPPORTING CHARACTERS’ DIALOGUES IN KNIVES OUT MOVIE - Fadilah, Fadilah; Habibah, Fiza Asri Fauziah (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2020)
This is the study of the use of category of hedging that is taken from the supporting characters’ dialogues in Knives Out movie. There are total 8 supporting characters who spoke with hedges contained in the dialogues. The method used is descriptive qualitative which describes the situation factually. There are 20 data found which are dialogues containing of hedging. Researcher uses the theory of the category of hedging by Yu which are modal hedges category, performative (mental hedges), pragmatic-marker hedges, and quantificational hedges. From the study, researcher found all category of hedging in the dialogues spoken by the supporting characters there 2 data found from modal hedges, 1 from both performative and quantificational hedges category, and the most found category is pragmatic-marker hedges which are 16 data found.